Antihyperglicemic Activity of Curcuma Xanthorrizha Roxb. Nanocurcuminoid Emulsion on Streptozotocin Induced Sprague-Dawley Rat - Irma Rahmayani; Laksmi Ambarsari; Mega Safithri (IPB University, 2016)
Curcuminoid, a natural compound isolated from Curcuma xanthorrhiza RoxB (Temulawak) has been reported to possess antioxidant, anti-inflammatory, anticancer, antimicrobial and anti-hyperglicemic properties. The curcuminoid is weakly soluble in water that restricts its bioavailability. This problem could be overcome by incorporating curcuminoid into solid lipid nanoparticles (SLN). Nanocurcuminoid was prepare by using homogenization-ultra sonication methods. Nanocurcuminoid obtained in this study was 523.5 nm in size and polydispersity index of 0.218 with entrapment efficiency of 24.2 %. Rats were made diabetic by induction of 50 mg / kg BW STZ, treated with the chosen formula (doses 5, 10, 20 mg/kg BW) orally for 15 days. Body weight and blood glucose levels were measured from day 0, 4th,7th,11th and 15th. The results showed that 15 days of daily treatment of 10 mg/kg BW nanocurcuminoid emulsion led to a reduction of blood glucose level by 30.93±14.90 % and body weight by 15.5±13.92 %. Curcuminoid formulated in solid lipid nanoparticles could suppress a decrease in body weight and lower blood glucose levels of rats.